Nonlinear reduced-order modeling and bifurcation analysis of whirl flutter in a rotor-nacelle system - Quintana, A.; Vasconcellos, R. [UNESP]; Throneberry, G.; Abdelkefi, A. (American Institute of Aeronautics and Astronautics (AIAA), 2020)
Whirl flutter is an aeroelastic instability that can be affected by structural or/and aerodynamic nonlinearities. This instability may lead to potentially dangerous behaviors. In this study, a nonlinear reduced-order model for a nacelle-rotor system, considering quasi-steady aerodynamics is implemented. First, a parametric study for the linear system is performed to determine the main aerodynamic and structural characteristics that affect the onset of instability. Multiple polynomial nonlinearities in the two degrees-of-freedom nacelle-rotor model are tested to simulate possible structural nonlinear effects including symmetric cubic hardening nonlinearities for the pitch and yaw degrees of freedom, purely yaw nonlinearity, purely pitch nonlinearity, and a combination of quadratic and cubic nonlinearities for both degrees of freedom. Preliminary results show that the presence of hardening structural nonlinearities introduces limit cycle oscillations to the system in the post-flutter regime. Moreover, the inclusion of quadratic nonlinearity introduces asymmetric oscillations and subcritical Hopf bifurcation.